2023
DOI: 10.1021/acs.jpcb.2c09050
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Decomposition of Uranium Oxychloride Phases in Oxygen-Exposed UCl3 Salt Compositions

Benjamin W. Tuffy,
Nancy R. Birkner,
Juliano Schorne-Pinto
et al.

Abstract: Complementary X-ray absorption fine structure (XAFS) spectroscopy and Raman spectroscopy studies were conducted on several UCl3 concentrations in several chloride salt compositions. The samples were 5% UCl3 in LiCl (S1), 5% UCl3 in KCl (S2), 5% UCl3 in LiCl–KCl eutectic (S3), 5% UCl3 in LiCl–KCl eutectic (S4), 50% UCl3 in KCl (S5), and 20% UCl3 in KCl (S6) molar concentrations. Sample S3 had UCl3 sourced from Idaho National Laboratory (INL), and all other samples were UCl3 sourced from TerraPower. The initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…It was found that the capillary sealing methodology successfully prevented degradation of the UCl 3 sample via oxidation and/or hydration (Figure S4). This was evident, as there are no U–O vibrational modes present in any of the spectra that were recorded between 300 and 1000 cm –1 ; in uranium oxychloride (UO 2 Cl 2 ), there is a strong temperature-dependent vibrational band located between 700 and 760 cm –1 . Additionally, there are no vibrational features near 450 cm –1 , which occurs in uranium dioxide [(U 4+ O 2 ) 0 ], and near 775 cm –1 , which occurs in uranyl [(U 6+ O 2 ) 2+ ] hydrates and oyxhydrates. …”
Section: Resultsmentioning
confidence: 96%
“…It was found that the capillary sealing methodology successfully prevented degradation of the UCl 3 sample via oxidation and/or hydration (Figure S4). This was evident, as there are no U–O vibrational modes present in any of the spectra that were recorded between 300 and 1000 cm –1 ; in uranium oxychloride (UO 2 Cl 2 ), there is a strong temperature-dependent vibrational band located between 700 and 760 cm –1 . Additionally, there are no vibrational features near 450 cm –1 , which occurs in uranium dioxide [(U 4+ O 2 ) 0 ], and near 775 cm –1 , which occurs in uranyl [(U 6+ O 2 ) 2+ ] hydrates and oyxhydrates. …”
Section: Resultsmentioning
confidence: 96%